Netizens’ Comment Analysis On The Tiktok Account “Barisan Pengusaha Pejuang” (A Netnographic Study On The Campaign Song Post Of Prabowo–Gibran) - Sukma, Anisa; Narti, Sri; Putra, Dilmai (Social Sciences Journal, 2025)
This study aims to analyze netizens’ comments on a campaign song video of presidential and vice-presidential candidates Prabowo–Gibran, posted by the TikTok account Barisan Pengusaha Pejuang. The research adopts a netnographic method with a qualitative descriptive approach, supported by the Computer Mediated Communication (CMC) theory to interpret interaction patterns in digital spaces. Data were collected using documentation techniques on 100 selected comments, followed by thematic coding and analysis. Findings reveal two main categories of comments: supportive or pro-Prabowo–Gibran comments, and sarcastic or critical comments. During the campaign period, most comments were positive, enthusiastic, and optimistic. However, after Prabowo–Gibran officially took office, the tone of the comments shifted toward sarcasm and public dissatisfaction, often triggered by unmet expectations regarding their performance or policies. This study illustrates how public opinion evolves in social media discourse and underscores the importance of digital sentiment in political communication.